Circular L-RNA aptamer promotes target recognition and controls gene activity. Issue 13 (7th July 2021) - Ji, Danyang; Lyu, Kaixin; Zhao, Haizhou; Kwok, Chun Kit
Abstract: Rational design of aptamers to incorporate unnatural nucleotides and special chemical moieties can expand their functional complexity and diversity. Spiegelmer (L-RNA aptamer) is a unique class of aptamer that is composed of unnatural L-RNA nucleotides, and so far there are limited L-RNA aptamer candidates and applications being reported. Moreover, the target binding properties of current L-RNA aptamers require significant improvement. Here, using L-Apt.4-1c as an example, we develop a simple and robust strategy to generate the first circular L-RNA aptamer, cycL-Apt.4-1c, quantitatively, demonstrate substantial enhancement in binding affinity and selectivity toward its target, and notably report novel applications of circular L-RNA aptamer in controlling RNA–protein interaction, and gene activity including telomerase activity and gene expression. Our approach and findings will be applicable to any L-RNA aptamers and open up a new avenue for diverse applications. Graphical Abstract: